2009
DOI: 10.5694/j.1326-5377.2009.tb02524.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal transmission of hepatitis B virus: an Australian experience

Abstract: Objective: To determine the rate of perinatal hepatitis B virus (HBV) transmission in an Australian setting and to identify maternal virological factors associated with highest risk of transmission. Design, participants and setting: A prospective, observational study of perinatal transmission of HBV. Participants were pregnant women attending Sydney South West Area Health Service antenatal clinics who tested positive for hepatitis B surface antigen (HBsAg), and their babies. All babies were routinely offered h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
268
2
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(284 citation statements)
references
References 20 publications
7
268
2
7
Order By: Relevance
“…In terms of a target viral load threshold, initial studies have suggested 2×10 7  IU/mL, although transmission of HBV at viral loads above 2×10 5  IU/mL has been observed 64. Others have suggested lower thresholds for transmission 65.…”
Section: Hbv Treatment Considerations In Women Of Childbearing Agementioning
confidence: 99%
See 1 more Smart Citation
“…In terms of a target viral load threshold, initial studies have suggested 2×10 7  IU/mL, although transmission of HBV at viral loads above 2×10 5  IU/mL has been observed 64. Others have suggested lower thresholds for transmission 65.…”
Section: Hbv Treatment Considerations In Women Of Childbearing Agementioning
confidence: 99%
“…Risk factors for immunoprophylaxis failure include high maternal HBV viral load, HBeAg positivity, incomplete HBV vaccination and a small risk of vaccine-escape mutants in the ‘a’ determinant region 64. The American Association for the Study of Liver Diseases recommends that all children born to HBsAg-positive mothers should be tested at ages 9–15 months for seroconversion 91.…”
Section: Postpartum Considerations In Hbv-infected Womenmentioning
confidence: 99%
“…There are numerous studies highlighting that even after the institution of active and passive immunoprophylaxis, higher maternal viral load is associated with a higher rate of MTCT 23–27. Immunoprophylaxis failure rates of between 8% and 32%28 29 have been reported in various prospective trials around the world and the most important factors associated with MTCT were maternal HBeAg positivity and high HBV DNA levels23 24 (table 1). Significant viremia predisposing to immunoprophylaxis failure had been considered to be serum HBV DNA levels of >8 log 10 copies/ml.…”
Section: Risk Factors For Mtctmentioning
confidence: 99%
“…Two additional doses of the hepatitis B vaccine are given at 1 and 6 months 46. This protocol has been shown to dramatically reduce the risk of MTCT to under 10% 23 25…”
Section: Management Of Hepatitis B In Pregnant Womenmentioning
confidence: 99%
“…If they test positive for the HBV surface antigen, further management should be initiated. Testing of the hepatitis B e antigen (HBeAg) and quantitative HBV DNA should be considered, as HBeAg positive mothers with high-maternal viraemia (>10 8 log copies/ml) appear to have a higher risk of MTCT, even with vaccination 3. Antiviral therapy in the third trimester has been advocated in these women, although data are limited.…”
Section: Commentarymentioning
confidence: 99%